Quantitative assessment of locomotive syndrome in Japanese office workers - Kurumi Tsuruta; Saori Yoshinaga; Tomoko Shiomitsu; Hiroki Tamura; Yoshinori Fujii; Etsuo Chosa (Japanese Society of Physical Fitness and Sports Medicine, 2018)
To reduce the risk of long-term care, it is important to prevent the functional decline of the locomotorium of elderly individuals early in life. This study aimed to clarify locomotive syndrome (LS) in Japanese office workers. The participants included 263 workers that mainly performed deskwork. Participants performed the LS risk test and completed a self-administered questionnaire survey that focused on lifestyle-related diseases, anxiety about physical strength, pain in the locomotorium, and health-related quality of life. Sixty participants (22.8%) were at risk for LS, and 17.5% of these participants were in their 20s. Of the participants at risk for LS (LS group), 30.0% had anxiety about physical strength, which was a significantly high ratio compared to the 14.3% of participants who expressed anxiety about physical strength, but were not at risk for LS (non-LS group) (χ2 = 6.479, p < .05). There were significant differences between risk for LS and pain in the back and hip joints (χ2 = 5.813, p < .05, χ2 = 4.895, p < .05). The LS group had a significantly lower mean physical summary score than the non-LS group (t = 3.286, p < .01). Thus, an intervention to prevent LS is important during the early stages, and signs such as pain in the locomotorium and anxiety about physical strength must not be overlooked.